Safety and efficacy of intravenous hydromorphone patient-controlled analgesia versus intramuscular pethidine in acute pancreatitis: An open-label, randomized controlled trial - Chen, Zhiyao; Jiang, Kun; Liu, Fei; Zhu, Ping; Cai, Fei; He, Yanqiu; Jin, Tao; Lin, Ziqi; Li, Qian; Hu, Cheng; Tan, Qingyuan; Yang, Xiaonan; et al. (Frontiers in Pharmacology, 2022)
Background: Hydromorphone patient-controlled analgesia (PCA) provides satisfactory postoperative pain therapy, but its effect has not been assessed in acute pancreatitis (AP). Aim: To assess the safety and efficacy of intravenous hydromorphone PCA for pain relief in AP. Methods: This open-label trial included AP patients admitted within 72 h of symptom onset, aged 18–70 years old, and with Visual Analog Scale (VAS) for pain intensity ≥5. They were randomized to receive intravenous hydromorphone PCA (0.05 mg/h with 0.2 mg on-demand) or intramuscular pethidine (50 mg as required) for three consecutive days. Intramuscular dezocine (5 mg on demand) was the rescue analgesia. The primary outcome was the change of VAS score recorded every 4 h for 3 days. Interim analysis was conducted by an Independent Data and Safety Monitoring Committee (IDSMC). Results: From 26 July 2019 to 15 January 2020, 77 patients were eligible for the intention-to-treat analysis in the interim analysis (39 in the hydromorphone group and 38 in the pethidine group). Baseline parameters were comparable between groups. No difference in VAS between the two groups was found. Hydromorphone PCA was associated with higher moderately severe to severe cases (82.1% vs. 55.3%, p = 0.011), acute peripancreatic fluid collections (53.9% vs. 28.9%, p = 0.027), more cumulative opioid consumption (median 46.7 vs. 5 mg, p < 0.001), higher analgesia costs (median 85.5 vs. 0.5 $, p < 0.001) and hospitalization costs (median 3,778 vs. 2,273 $, p = 0.007), and more adverse events (20.5% vs. 2.6%, p = 0.087). The per-protocol analysis did not change the results. Although a sample size of 122 patients was planned, the IDSMC halted further recruitment as disease worsening or worse clinical outcomes between the groups in the interim analysis. Conclusion: Hydromorphone PCA was not superior to pethidine in relieving pain in AP patients and might have worse clinical outcomes. Therefore, its use is not recommended. Clinical Trial Registration: Chictr.org.cn. ChiCTR1900025971